Expression of Circ_Satb1 Is Decreased in Mesial Temporal Lobe Epilepsy and Regulates Dendritic Spine Morphology - Gomes-Duarte, Andreia; Venø, Morten T.; de Wit, Marina; Senthilkumar, Ketharini; Broekhoven, Mark H.; van den Herik, Joëlle; Heeres, Fleur R.; van Rossum, Daniëlle; Rybiczka-Tesulov, Mateja; Legnini, Ivano; van Rijen, Peter C.; van Eijsden, Pieter; et al. (Frontiers in Molecular Neuroscience, 2022)
Mesial temporal lobe epilepsy (mTLE) is a chronic disease characterized by recurrent seizures that originate in the temporal lobes of the brain. Anti-epileptic drugs (AEDs) are the standard treatment for managing seizures in mTLE patients, but are frequently ineffective. Resective surgery is an option for some patients, but does not guarantee a postoperative seizure-free period. Therefore, further insight is needed into the pathogenesis of mTLE to enable the design of new therapeutic strategies. Circular RNAs (circRNAs) have been identified as important regulators of neuronal function and have been implicated in epilepsy. However, the mechanisms through which circRNAs contribute to epileptogenesis remain unknown. Here, we determine the circRNA transcriptome of the hippocampus and cortex of mTLE patients by using RNA-seq. We report 333 differentially expressed (DE) circRNAs between healthy individuals and mTLE patients, of which 23 circRNAs displayed significant adjusted p-values following multiple testing correction. Interestingly, hippocampal expression of circ_Satb1, a circRNA derived from special AT-rich sequence binding protein 1 (SATB1), is decreased in both mTLE patients and in experimental epilepsy. Our work shows that circ_Satb1 displays dynamic patterns of neuronal expression in vitro and in vivo. Further, circ_Satb1-specific knockdown using CRISPR/CasRx approaches in hippocampal cultures leads to defects in dendritic spine morphology, a cellular hallmark of mTLE. Overall, our results identify a novel epilepsy-associated circRNA with disease-specific expression and previously unidentified cellular effects that are relevant for epileptogenesis.